Characterization of Susceptibility Variants of Influenza Virus Grown in the Presence of T-705 - Tohru Daikoku; Yoshihiro Yoshida; Tomoko Okuda; Kimiyasu Shiraki (Elsevier, 2014)
Abstract.: T-705 (favipiravir) is a potent inhibitor of RNA polymerases of influenza viruses. Susceptibility variants were isolated during passages in the presence of T-705. Nine variants with 0.4 to 2.1 times the 50% inhibitory concentration for plaque formation of the parent A/PR/8/34 (H1N1) strain had amino acid variations in the PB1, PB2, and PA genes of the RNA polymerase complex. However, the variation patterns in the RNA polymerase complex indicated that T-705 does not work as a mutagen, and resistant mutants were not isolated, possibly because a mutation leading to resistance would be lethal to the RNA polymerase function. Keywords:: influenza virus, T-705, favipiravir